KAJIAN EXPERIMENTAL TENTANG UMUR PERAWATAN BETON MEMAKAI LEMBARAN PLASTIK DITINJAU TERHADAP KUAT TEKAN BETON - Azhari -; Suprasman -; H Gusyafri; Dedy Irawan Putra (Jurnal APTEK, 2012)
Among the factors that influence the behavior of the compressive strength of concrete after placing of concrete is the presence/absence of concrete curing and how it's cure done. Concrete curing intended as an effort to maintain the continuity of the hydration process of cement with water to binder aggregate until a certain time. Loss of water during the hydration process can reduce the quality of concrete, especially concrete compressive strength. Meanwhile in the field (on projects that are less supervision) are often encountered - especially in the column - after the mold is opened (with the opening of varying ages), concrete is left alone without curing. This research review the extent to which variations in the treatment of curing post placing of concrete affect the compressive strength of concrete. For it was made in the form of cylindrical concrete specimens with varying age of treatment (by way of concrete with a plastic cover) after the mold is opened, which is 1 day, 3 day, 7 days, 14 days, 21 days, and 28 days. In addition to the specimens was made with the standard curing for comparison.